Functional, rheological and sensory properties of a food from honey and aloe vera - Suarez-Ramos, Claudia Andrea; Vidal-Prado, Seidy Vanessa; Morales-Hormiga, Carlos Hernán; Roa-Acosta, Diego Fernando; Nieto-Calvache, Jhon Edinson (Frontiers in Sustainable Food Systems, 2023)
The consumption of honey products has increased in recent years, largely due to the pandemic caused by SARS-CoV-2 (COVID-19). The objective of this work was to evaluate the functional, color, rheological and sensory properties of honey (H) and honey mixtures with aloe vera (AV). Among the functionality evaluated, the ability to stabilize DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2′-Azino-bis(3-thylbenzothiazoline-6-sulfonic acid)) radicals was determined, as well as the reducing capacity and the content of phenolic compounds. Rheological behavior was analyzed by flow and oscillatory tests. Finally, product acceptance was analyzed by means of a sensory panel. The results showed that honey, AV and the mixtures presented antioxidant activity between 52.5 and 57 mg trolox/g sample, (DPPH method), between 1,666 and 1765 μg trolox/g sample (ABTS method), between 217 and 506 μg trolox/g sample (FRAP method) and between 62.5 and 164.6 mg GAE/100 g sample (phenolic compounds in gallic acid equivalents, GAE). The values obtained were in the order of those reported in the literature for these products. Rheological tests showed a pseudoplastic flow type in the honey and AV mixtures, and a Newtonian tendency for the honey. In addition, the oscillatory tests showed a dependence of the oscillation frequency on G’ and G.” It can be concluded that the mixtures of honey and AV maintain functionality in terms of antioxidant properties after processing and are also accepted by consumers in terms of taste, smell, color and texture.